(untitled) (Світ фінансів, 2017)
Литвин М. В. Досвід Японії у стимулюванні розвитку регіонів. Проаналізовано японський досвід розвитку регіонів в контексті забезпечення сталого розвитку. Узагальнено періодизацію становлення та розвитку національної економічної моделі Японії. Досліджено досвід формування дохідної частини місцевих бюджетів. Lytvyn M. Japanese experience in stimulate of regions development. The features of the Japanese experience of regions development in the context of providing of steady development are analysed. The division into periods of the becoming and development of the national economic model of Japan is generalized. The experience of forming the profitable part of the local budgets is investigated.